Microleakage and SEM analysis of flowable resin used as a sealant following three fissure preparation techniques--an in vitro study - Chaitra, T R; Subba, Reddy V V; Devarasa, G M; Ravishankar, T L (The Journal of clinical pediatric dentistry, 2011)
Preventive procedures using pit and fissure sealants are one of the important aspects of pediatric dental practice. The objectives of this in vitro study were to comparatively evaluate microleakage and resin tag penetration of a flowable resin used as a sealant on molars after preparation with Conventional, Enameloplasty and Fissurotomy techniques. A total of 48 teeth were divided into 3 groups (n-16). Group A (CST), Group B (EST), and Group C (FT). Following the fissure preparation sealant was applied as per manufacturer's instructions. 8 samples in each group were used for Microleakage and Resin tag analysis. Microleakage analysis was done under Stereomicroscope after Methylene blue dye immersion by using scoring system. The resin tag analysis was done by measuring the length of resin tags on scanning electron microscope (SEM) images consisting of 10 microm scale taken under optical zoom of 2000 X. Significantly lesser microleakage score (P < 0.01) and longer resin tag penetration (P < 0.001) observed in EST (mean score 0.5 +/- 0.53) & (12.19 +/- 1.93 microm) when compared to CST (mean score 1.75 +/- 0.89) & (5.96 +/- 1.84 microm) and FT (mean score 1.5 +/- 0.53) & (6.76 +/- 1.82 microm) which showed more microleakage and short resin tags. No statistical significance between CST and FT was found. EST has proven to be an excellent method for preparation of pits and fissures when Flowable composite is used as a sealant because of its lesser microleakage and longer resin tag penetration.